Resistance And Colonial Discourse In Maishe Maponya’s The Hungry Earth (Journal of Namibian Studies : History Politics Culture, 2023)
This paper investigates resistance and colonial discourse in Maishe Maponya’s play The Hungry Earth to reveal the role that imperialism played in South Africa to dominate oppress and silence the African people. For this purpose, the theoretical framework of postcolonial theory is adopted throughout the paper to reveal how imperialism and apartheid regimes have dominated and subjugated Africans for a long period and shed light on the sufferings of Africans, especially mine workers. Using a postcolonial theory, this article makes the African sounds heard even if their sounds are voices made by their boots purposely used to create their discourse.